Grafismo rupestre paleolítico de la Cueva del Conde (Tuñón, Santo Adriano, Asturias) - Fernández Rey, Alba; Adan Álvarez, Gema Elvira; Arbizu, Miguel; Arsuaga, Juan Luis (Zephyrvs, 2009)
RESUMEN: LOS grabados de la Cueva del Conde (Tuñón, Santo Adriano, Asturias) se sitúan en tres zonas: dos en el entrante más septentrional de la cavidad y el tercer conjunto en la entrada en alto de la pared meridional. Se les asigna una cronología Aurifiaciense, con similitudes de otros grabados asturianos como los de la Viña (Manzaneda, Oviedo, Asturias). ABSTRACT: The engravings of Conde Cave (Tuñón, Santo Adtiano, Asturias) are placed in three areas: two in the most northern incoming of the cave and the third set in a little incoming placed high in the southern wall. The supposed age for these engravings is Aurignacian, with similarity with other engravings of caves from Asturias, as La Viña Cave (Manzaneda, Oviedo, Asturias).